Analisis Pengaruh Game Online Free Fire Terhadap Karakter Disiplin, Tanggung Jawab, dan Peduli Sosial Siswa Kelas V SDN 184 Pekanbaru - Yulinda Agita Putri; Gustimal Witri; Muhammad Fendrik (Universitas 45 Surabaya, 2024)
This study aims to analyze the impact of the online game Free Fire on the character of fifth-grade students at SDN 184 Pekanbaru. The research method used is qualitative with a descriptive approach. The subjects of the study consist of students addicted to the game, students who play the game moderately, and students who do not play the game. Data were collected through interviews, observations, and documentation. The results show that the online game Free Fire negatively impacts the students' discipline, responsibility, and social care. Students addicted to the game tend to have difficulties managing time, completing tasks, and social interactions. Conversely, students who do not play the game exhibit better discipline, responsibility, and more positive social interactions. The role of parents and teachers is crucial in mitigating these negative effects through proper supervision, guidance, and setting limits. The proposed solutions include cooperation between the school and parents, education on wise time use, and the development of more beneficial hobbies. It is hoped that these measures will minimize the negative impact of the online game Free Fire on students' character.